Effects of Exercise on Sleep Quality in Pregnant Women: A Systematic Review and Meta-analysis of Randomized Controlled Trials - Shu-Ya Yang; Shou-Jen Lan; Yea-Yin Yen; Yen-Ping Hsieh; Pei-Tseng Kung; Shao-Huan Lan (Elsevier, 2020)
Summary: Purpose: Sleep quality was considered a priority concern facing pregnant women. Conventional wisdom argues that good sleep quality benefits pregnant women and their fetuses. The aim of this study is to assess the effects of a specific exercise program on the　sleep quality in pregnant women.Methods: Searches were executed in seven databases since their inceptions until February 28, 2019, for randomized controlled trials evaluating the effects of an exercise program on the sleep quality and insomnia in pregnant women. A random-effects model was applied for meta-analysis, and odds ratio, mean differences (MDs), and 95% confidence intervals (CIs) are shown as parts of outcomes.Results: Seven studies were included for meta-analysis. Compared with their not-exercising counterparts, analyses showed that regularly exercising women had significantly enhanced sleep quality, with an odds ratio of 6.21 (95% CI, 2.02-19.11;p = .001; I2 = 80.2%), with a standardized MD of −0.93 (95% CI, −1.19 to −0.67; p < .001; I2 = 30.0%). However, exercising women showed no significant insomnia improvement, with an standardized MD of −2.85 (95% CI, −7.67 to 1.98; p = .250; I2 = 97.0%), relative to their not-exercising counterparts.Conclusion: This research indicated that exercise has a positive impact on the sleep quality of pregnant women. Despite the aforementioned positive impact on sleep quality, the present study did not find evidence to support that exercise may also improve insomnia for pregnant women. Keywords: exercise, meta-analysis, pregnant women, sleep, sleep initiation and maintenance disorders